PENDAMPINGAN UMKM BAKSO MBURU CUKUP DALAM PENGUATAN IDENTITAS USAHA DAN TRANSFORMASI DIGITAL - Tiko Novitryan Hidayanto; Florence Agustin; Siti Nur Hidayatul Lailiah; Susanti Dwi Ilhami (Jurnal Padamu Negeri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in improving the community's economy. However, many business actors still face obstacles in business branding and digitalization. One of the MSMEs experiencing these problems is Bakso Mburu Cukup MSME in Turusgede Village, which did not yet have a visual business identity, digital business location, and non-cash payment system. This Kuliah Kerja Usaha (KKU) activity aimed to improve business identity and service quality through branding strengthening and digital transformation. The implementation methods used observation, mentoring, implementation, and evaluation stages. The programs carried out included creating business banners and logos, registering business locations on Google Maps, and implementing the QRIS digital payment system. The results showed that the installation of banners and business logos increased business visibility and attractiveness, making it easier for the community to recognize the MSME location. In addition, registering the business location on Google Maps made it easier for customers to find the business digitally, while implementing QRIS improved the convenience and efficiency of payment transactions. Based on the evaluation results, the program succeeded in improving service quality, customer convenience, and the number of daily customers. Overall, the KKU activity successfully provided solutions to business problems through branding strengthening and service digitalization, thereby helping improve the competitiveness of MSMEs in the digital era.